2013
DOI: 10.1128/cvi.00538-13
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Commercial Enzyme-Linked Immunosorbent Assay for the Diagnosis of Bovine Tuberculosis from Milk Samples from Dairy Cows

Abstract: Milk samples from dairy cows provide a ready source of material for measuring antibody responses to Mycobacterium bovis antigens. In this study, we evaluated the IDEXX enzyme-linked immunosorbent assay (ELISA) for the measurement of antibody responses to M. bovis antigens MPB70 and MPB83 in milk samples from New Zealand cattle. Test sensitivities for individual milk and serum samples were assessed in samples collected from 44 M. bovis-infected cows, and test specificities were assessed in milk samples collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 15 publications
2
18
0
Order By: Relevance
“…31 Also, it would be missed; apparently, their benefit through an examination of a few diseased cattle that persist at large groups. 20 The results of Tables 2 and 3 revealed that in Wasit province, the morbidity rate was more than this reported in Dhi-Qar province. Although, the role of local spread of bTB in some areas is not well understood, bTB testing had a significant impact on the expansion and long distance spread of disease, especially on transmission to areas with relatively low incidence.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…31 Also, it would be missed; apparently, their benefit through an examination of a few diseased cattle that persist at large groups. 20 The results of Tables 2 and 3 revealed that in Wasit province, the morbidity rate was more than this reported in Dhi-Qar province. Although, the role of local spread of bTB in some areas is not well understood, bTB testing had a significant impact on the expansion and long distance spread of disease, especially on transmission to areas with relatively low incidence.…”
Section: Discussionmentioning
confidence: 72%
“…Thus, IDEXX ELISA had a sensibility to detect the antibodies in blood more than in milk, and several causes may be concluded in the interpretation of this difference such as the individual differences in animal's antibody responses, lactation stage, time of milk collection, herd size, proportion of milk dilution, cutoff level changing, and the producing of nonspecific antibody responses to test antigens. 20 However, the test sensitivity is increased markedly with severity of the disease. 27 Also, the high relationship among an antibody's reactions in milk and blood had been reported, at same animal, in bTB and John's disease.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the economic consequences associated with M. bovis infections in cattle, as well as its zoonotic potential, methods for quickly and accurately identifying infected cattle are of considerable importance. One such method is an enzyme-linked immunosorbent assay (ELISA) developed by IDEXX Laboratories (Westbrook, ME), which allows for the rapid detection of M. bovis -specific antibodies in bovine serum or milk samples 5 6 . This assay detects antibodies to the antigenic proteins MPB70 (where “MPB” is an acronym for p rotein from M .…”
mentioning
confidence: 99%
“…The IDEXX ELISA has been tested on serum and milk samples from cattle that are not infected with M. bovis , and has been found to have a specificity of approximately 98%—that is, the test gives a positive result for only 2% of uninfected cattle 5 6 . The sensitivity of the ELISA has been evaluated using cattle that were verified to be infected with M. bovis using independent tests.…”
mentioning
confidence: 99%
“…After a wash step, detection of anti-heartworm specific antibody was performed using a secondary anti-species antibody horseradish peroxidase conjugate (1:2000 dilution, Jackson ImmunoResearch, West Grove, PA). Following a wash step and addition of substrate, plate absorbance optical density (OD) values were recorded and sample-to-positive ratios (S/P; sample OD divided by positive control OD) were calculated for each sample (sample OD-negative control OD]/positive control OD-negative control OD) (Buddle et al 2013). Samples with S/P ratios ≥ 0.5 were positive.…”
Section: Heartworm Antibody Testingmentioning
confidence: 99%